Quality of Genom in Type II Diabetes Mellitus Patients in Viewed of Temperature, Storage Duration, Number of Leukocyte - Puspitasari Puspitasari; Evi Rinata; Rohman Dijaya; Siska Aprilia; Dina Trikumalasari; Livia Nur Azzah; Qilmia Fanani; Miftahul Mushlih; Andika Aliviameita; Dian Delta (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2019)
Type II Diabetes Mellitus is a disorder caused by genetic and environmental factors. Molecular analysis of T2DM abnormalities has been carried out. But the analysis in sample preparation especially the stages of DNA isolation has not been done much. The aims of this study are to investigate the effect of temperature, storage duration and level of white blood cell (WBC) with Genome Quality in T2DM. The treatment (n:10) which were divided into several tubes and then stored at 4 °Ϲ, 25 °Ϲ and 32 °Ϲ for 21 days. To determining storage duration effect, we use periodically isolation of DNA (3, 15 and 30 days) after sampling. The effect of WBC with DNA quality was carried out using 17 samples. DNA isolation was done by the DNA Isolation Kit manual without modification and then tested qualitatively and quantitatively. Based on this research, it can be concluded there is a correlation between the numbers of WBC with DNA quality. The higher the number of WBC, the higher DNA concentration (r: 0.818. p value: 0.000). The concentration of DNA at a temperature of 4°Ϲ (135.1 ± 165.2 ng / µl) was higher compared with the temperature treatment 25 ° Ϲ (29.7 ± 36.5 ng / µl) and 32 ° Ϲ (22.14 ± 7.13 ng / µl) (p